Deep Brain Stimulation Hardware Infections: A Case Series - Kaptan, Hulagu; Yuzbasi, Furkan; Özturk, Fatih; Vayvada, Haluk (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: The device-related infections and erosion of the surgical wound site are special circumstances among complications of deep brain stimulation (DBS). AIM: We aimed to discuss different aspects of hardware infections and contribute to the literature by presenting our treatment methods on four patients. MATERIAL AND METHODS: This study was carried out in the Department of Neurosurgery, School of Medicine Hospital, Dokuz Eylul University. Four DBS cases were included in the study, and a retrospective study was performed. RESULTS: Electrode placement to bilateral subthalamic nuclei was performed due to Parkinson’s Disease to all four patients. One of the patients was undergone surgical wound site revision 6 times and device removal at last due to device-related infection and erosion of the surgical wound site. The second patient was undergone surgical wound site revision for 2 times and device removal at last due to device-related infection and erosion of the surgical wound site. The third patient had a collection subcutaneously, where the pulse generator was placed. The collection was aspirated. The fourth patient was undergone surgical wound site revision and device removal at last due to device-related infection and erosion of the surgical wound site. All four patients were given IV antibiotics. CONCLUSION: For the treatment of DBS device-related infections, a long-term IV antibiotherapy is a suitable option before the decision of device removal.